Practical guidance for mismatch repair-deficiency testing in endometrial cancer. (13th October 2016) - Stelloo, E.; Jansen, A. M. L.; Osse, E. M.; Nout, R. A.; Creutzberg, C. L.; Ruano, D.; Church, D. N.; Morreau, H.; Smit, V. T. H. B. M.; van Wezel, T.; Bosse, T.
Abstract: Background: Mismatch repair (MMR)-deficiency analysis is increasingly recommended for all endometrial cancers, as it identifies Lynch syndrome patients, and is emerging as a prognostic classifier to guide adjuvant treatment. The aim of this study was to define the optimal approach for MMR-deficiency testing and to clarify discrepancies between microsatellite instability (MSI) analysis and immunohistochemical (IHC) analysis of MMR protein expression. Patients and methods: Six hundred ninety- six endometrial cancers were analyzed for MSI (pentaplex panel) and MMR protein expression (IHC). Agreement between methodologies was calculated using Cohen's Kappa. MLH1 promoter hypermethylation, dinucleotide microsatellite markers and somatic MMR and POLE exonuclease domain (EDM) gene variants (using next-generation/Sanger sequencing) were analyzed in discordant cases. Results: MSI was found in 180 patients. Complete loss of expression of one or more MMR proteins was observed in 196 cases. A PMS2- and MSH6-antibody panel detected all cases with loss of MMR protein expression. The results of MSI and MMR protein expression were concordant in 655/696 cases (kappa = 0.854, P < 0.001). Ambiguous cases ( n = 41, 6%) included: subclonal loss of MMR protein expression ( n = 18), microsatellite stable or MSI-low cases with loss of MMR protein expression ( n = 20), and MSI-low or MSI-high cases with retained MMR protein expression ( n = 3). Most of these cases could be explained by MLH1 promoter hypermethylation. Five of seven cases with solitary loss of PMS2 or MSH6 protein expression carried somatic gene variants. Two MSI-high cases with retained MMR protein expression carried a POLE -EDM variant. Conclusion: MSI and IHC analysis are highly concordant in endometrial cancer. This holds true for cases with subclonal loss of MMR protein expression. Discordant MMR-proficient/MSI-high cases (<1%), may be explained by POLE -EDM variants.